2011
DOI: 10.1007/s11094-011-0616-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and flavonoid composition of the new pancreoprotective preparation Pancreophyt

Abstract: The antioxidant activity of the new pancreoprotective plant preparation Pancreophyt has been studied experimentally on an animal model of acute chloroethane-induced pancreatitis. The flavonoids luteolin-7-glycoside, apigenin, hpyeroside, rutin, vitexin, dihydroquercetin, and quercetin in addition to cinnamic, gallic, caffeic, and cichoric acids were observed in the phytopreparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Pyrolae herba functions by expelling wind and removing dampness, and promoting blood circulation for the regulation of menstruation and the relief of pain (14,15). In modern pharmacological studies, the active components of Pyrolae herba such as chimaphilin, ursolic acid and hyperoside had previously been shown to possess anti-inflammatory, antioxidant and antibacterial properties (16)(17)(18)(19)(20)(21). Recent studies have suggested that ursolic acid inhibits cell proliferation and downregulates the expression of anti-apoptotic and metastatic gene products, potentiating antitumor activity (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolae herba functions by expelling wind and removing dampness, and promoting blood circulation for the regulation of menstruation and the relief of pain (14,15). In modern pharmacological studies, the active components of Pyrolae herba such as chimaphilin, ursolic acid and hyperoside had previously been shown to possess anti-inflammatory, antioxidant and antibacterial properties (16)(17)(18)(19)(20)(21). Recent studies have suggested that ursolic acid inhibits cell proliferation and downregulates the expression of anti-apoptotic and metastatic gene products, potentiating antitumor activity (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%